2020
DOI: 10.1055/s-0040-1716710
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Neuroprotection of the Preterm Brain: Current Evidence and Perspectives

Abstract: Despite improvements in viability, the long-term neurodevelopmental outcomes of preterm babies remain serious concern as a significant percentage of these infants develop neurological and/or intellectual impairment, and they are also at increased risk of psychiatric illnesses later in life. The current challenge is to develop neuroprotective approaches to improve adverse outcomes in preterm survivors. The purpose of this review was to provide an overview of the current evidence on pharmacological agents target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 157 publications
(221 reference statements)
0
1
0
Order By: Relevance
“…One such drug is caffeine, which is used to treat apnea of prematurity. In longitudinal studies, caffeine has been shown to improve cognitive outcomes [7][8][9][10][11][12]. However, the mechanism of protection is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One such drug is caffeine, which is used to treat apnea of prematurity. In longitudinal studies, caffeine has been shown to improve cognitive outcomes [7][8][9][10][11][12]. However, the mechanism of protection is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, so far neuroprotective efficacy of melatonin in animals, either given prenatally through the mother or postnatally to the infant, needs to be shown in humans before we can widely apply this as a clinical neuroprotection strategy [ 4 ].…”
mentioning
confidence: 99%